Difficulties Faced by Eleventh Grade Students in Translating English Narrative Texts into Indonesian at SMA Swasta Katolik Mariana Medan - yuni manullang; Kammer Sipayung; Dewi Silalahi (Visi Sosial Humaniora, 2026)
This study aimed to investigate the types of translation difficulties faced by eleventh-grade students in translating English narrative texts into Indonesian and to identify the factors causing these difficulties. The research employed a descriptive qualitative method, using translation sheets and interview transcripts as the primary data sources. The findings revealed that students experienced three main types of difficulties: lexical, grammatical, and semantic, with lexical difficulties being the most dominant (42.5%), followed by grammatical (32.5%) and semantic difficulties (25%). The factors causing these difficulties were classified into linguistic factors, including limited vocabulary, grammar and sentence structure problems, lack of contextual understanding, and reliance on literal translation, as well as non-linguistic factors such as fear of making mistakes, low self-confidence, and lack of practice. The study concluded that both linguistic competence and psychological factors significantly influenced students’ translation performance, suggesting that improvement in vocabulary, grammar mastery, contextual understanding, and learning support is essential to enhance students’ translation skills. Keywords: Translation difficulties; English narrative texts, lexical, grammatical, semantic, linguistic and non-linguistic factors.